Education Watch 2001 : renewed hope daunting challenges - Chowdhury, A Mushtaque R; Nath, Samir R; Choudhury, Rasheda K; Manzoor Ahmed (Research and Evaluation Division, Brac, 2019)
The Education Watch came into existence in 1998. The first report of the Watch titled Hope not Complacency: Stale of Primary Ed11cation in Bangladesh was published in 1999. The main purpose of this report was to look into internal efficiency of primary education sub-system. Although there were some radical revel<~tions, the report was an instant success. The stakeholders, the practitioners, the development partners and the civil society representatives accepted the report with enthusiasm. Encournged by the success and acceptance of the first Watclt we decided to devote the second Walcll to quality aspects of primary education. As it was not possible to deal with all the quality indic<~tors of primary education we picked up two mnjor issues, assessment of lenming achievement of students and tcacher education. The first Watch found out that there was considerable exp:-~nsion of prim:-~ry education nnd near gender parity. It can not, however, be said that we achieved similnr success so fM as qu<~lity is concerned. Quality assurance remJins J distnnt go;~ I. r:or the third Watclt we have decided to revisit the intern.1l efficiency scenario. Two additional are.1s included in this Waldt <~rc private cost of educc1tion c111d income nnd expenditure of schools, nnd literacy. Findings of the internal efficiency indicators showed consistency with the first Watch. There was reasonnble qunntit<~tiv<' expnnsion. 13ut qunlity rem<~ined illusive. The government, the policy plnnncrs c1nd the stakeholders need to be concerned ;~bout how to improve quality in t;~ndem with qu<~ntit;~tivc exp<lnsion. The other arcn of concern i~ the privntc cost of schooling. Primnry educntion is the constitutionnl obligntion of the government. It is supposed to be free nne! universnl. Unfortunately there is cost involved which v;~ries with school type. Pnrents and guarclinns are to pny ilbout half of the totnl costs of primnry eclucntion. This is a cnuse of concern because it mny restrict nccess to primnry education. As in the pnst 13RAC Rcsenrch <lncl Evilluntion Division under the nble leadership of Dr. A. M. R Chowdhury, Director Resenrch 13RAC ilnd Mr. Snmir Ranjnn Nnth, Senior Resenrch Statisticinn were responsible for fidd investigntion nnd prcpar<~tion of the report. !3oth of them deserve npprecintion for the commendnble work done. Dr. Manwor Ahmed former Director of UNICEF was also nssocinted with the prepnration of this report. I nm very thnnkful to him.